Intracranial Pressure and Biochemical Indicators of Brain Damage: Follow-up Study - Koršič, Marjan (Croatian Medical Schools, 2006)
AIM: To investigate the relation between metabolic parameters of the brain tissue, as direct indicators of real metabolic conditions within the brain, and intracranial pressure, as the consequence of pathophysiological changes. METHODS: Twelve patients with closed head injuries were followed up for 24 hours after injury. A Codman parenchymal intracranial pressure and a Neurotrend electrode were inserted within 3 hours after injury to monitor parenchymal intracranial pressure, brain tissue partial oxygen pressure (P(br)O(2)), brain tissue partial carbon dioxide pressure (P(br)CO(2)), pH, and brain tissue temperature. Data detected at 8-hourly intervals were compared with repeated measures analysis of variance. RESULT: At the initial observation, the mean value of intracranial pressure was 22.2 ± 3.2 mm Hg. Although it increased at the second and decreased at the third measurement, the differences between the measurements were not significant (P = 0.320). The value of P(br)CO(2) was increased from the beginning (63.3 ± 6.0 mm Hg), whereas P(br)O(2) was within the normal range at the first measurement (38.9 ± 6.9 mm Hg), but significantly decreased after 8 hours (P = 0.004), remaining low at later time points. CONCLUSION: After brain injury, changes in P(br)CO(2) are visible earlier than those in P(br)O(2). Improvement in intracranial pressure values did not necessary mean improvement in the brain tissue oxygenation. In addition to intracranial pressure, P(br)O(2,) P(br)CO(2) and pH should also be monitored, as they directly reflect the real metabolic conditions within brain tissue and may be used in predictions about the outcome and possible therapeutic approaches.